2015
DOI: 10.1002/sdtp.10455
|View full text |Cite
|
Sign up to set email alerts
|

19.1: OLED Power Reduction Algorithm Using Gray‐level Mapping Conversion

Abstract: This paper presents a new OLED power reduction algorithm. It computes the optimal power reduction level by modifying the gray-level mapping curve between input and output signals based on the image quality metric. Therefore, it does not need any circuit modification or additional circuits for the power reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In this section, we compare the proposed method with previous studies, PCCE [11] and two BS [8], [13] methods. The PCCE is one of the most widespread CE techniques, and the two BS techniques presented in [8] and [13] reduce the brightness by modulating the Y (YCbCr) and L* (CIELAB) components, respectively. Because the three methods commonly have a similar approach that reduces the brightness, we chose them for comparison.…”
Section: B Comparison With Previous Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we compare the proposed method with previous studies, PCCE [11] and two BS [8], [13] methods. The PCCE is one of the most widespread CE techniques, and the two BS techniques presented in [8] and [13] reduce the brightness by modulating the Y (YCbCr) and L* (CIELAB) components, respectively. Because the three methods commonly have a similar approach that reduces the brightness, we chose them for comparison.…”
Section: B Comparison With Previous Studiesmentioning
confidence: 99%
“…11(f)-11(h) show the distribution of ΔL*. The white, red, green, and blue colored distributions indicate the proposed and previous methods of [11], [8], and [13], respectively. On one hand, in the case of the proposed method, it is observed that a majority of the ΔL* values are zero and are distributed near zero.…”
Section: B Comparison With Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations